Empowering Culinary Micro, Small, and Medium Enterprises through Digital Marketing: A Qualitative Study in Mataram City, Indonesia - Desi Suryati; Rohmiati Amini; Meiyanti Widyaningrum; Samsuriadi Samsuriadi (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2023)
This study explores how digital marketing strategies can enhance the competitiveness andsustainability of culinary Micro, Small, and Medium Enterprises (MSMEs) in Mataram City,Indonesia. The research responds to the structural challenges faced by local enterprises in thepost-pandemic era, particularly the need for digital transformation in marketing and customerengagement. A qualitative approach was employed through interviews, observation, and systemprototyping. The study developed and tested a digital marketing model integrating websitebased promotion tools with social media and marketplace platforms such as Instagram,WhatsApp, Shopee, and Tokopedia. The findings indicate that the adoption of digital marketingimproves visibility, customer interaction, and transaction efficiency, enabling MSMEs to expandtheir market reach and strengthen business resilience. The research concludes that digitalmarketing serves not only as a technological innovation but also as a strategic empowermenttool that fosters digital literacy and entrepreneurial adaptability among MSME actors. Theimplications of this study emphasize the need for continued digital capacity-building programsand government facilitation to accelerate inclusive economic recovery at the regional level